A Study on the Effects of Psychiatric Nursing Education on Empathy and Self-Actualization in Nursing Students from Different Schools: Enhancing Empathy and Self-Actualization in Psychiatric Nursing Education (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Empathy is a capability that can be established and mastered by proper instruction and practice. While we recognize the role of empathy for nurses, less is understood regarding its effect on the degree of empathy for students at the Faculty of Patient Care at the Alexandria University. The objective of the thesis was to estimate an improvement of empathy in bachelor's nursing students for patients with mental disorder before and after a clinical nursing and schooling. It was concluded that a study in clinical care and behavioral wellbeing would increase the empathy of infant students Psychiatrists, Nursing, and other topics were explored in this report. the study which discussed about Psychiatric nurse with a license, In the case of India, psychiatric nursing, Realization of one's potential, The importance of empathic nursing treatment, In nurses, Self-actualization is important. Empathy and self-actualization for psychiatric care workers should be improved. Educational programme for psychiatric nurses, Treatments for Psychiatric Illnesses, Care in conjunction with an already available outpatient treatment